Effects of urban green exercise on mental health: a systematic review and meta-analysis - Hu, Guidan; Luo, Qingyuan; Zhang, Peng; Zeng, Hao; Ma, Xiujie (Frontiers in Public Health, 2025)
As global urbanization accelerates, concerns regarding the mental health of urban residents have become increasingly prominent. Urban green exercise, a non-pharmacological intervention integrating exposure to nature with physical activity, has gained considerable attention due to its potential mental health benefits. However, systematic evidence synthesizing the specific effects and underlying mechanisms of urban green exercise on mental health remains limited. Following strict adherence to PRISMA guidelines, systematic searches of PubMed, MEDLINE, Embase, the Cochrane Library, and Web Of Science identified 15 RCTs involving urban green spaces, comprising 980 participants aged 18 years and older. Methodological quality was evaluated using the Cochrane RoB 2.0 tool. Meta-analysis using standardized mean difference (SMD) was conducted using Stata 17.0, while subgroup and regression analyses were performed to explore moderating factors, including intervention period, frequency, duration per session, exercise intensity (METs), and gender. A moderate and statistically significant positive impact of urban green exercise on mental health was found (SMD = −0.40; 95% CI = −0.56 to −0.25; p < 0.001), with low between-study heterogeneity (I2 = 33.9%). The most pronounced effects were associated with short-duration interventions (<12 weeks), interventions conducted at least three times weekly, session durations of 20 min or less, and low-to-moderate intensity (≤3 METs). Greater benefits were observed among female participants. This systematic review provides robust empirical support for the mental health benefits of urban green exercise in adult urban populations, highlighting the efficacy of short-duration, high-frequency, moderate-intensity intervention models. These findings offer evidence-based insights to inform urban public health policy and green space planning, emphasizing the need to enhance the accessibility and utilization of urban green spaces. Further high-quality RCTs with larger sample sizes are recommended to further validate long-term effects and elucidate underlying mechanisms.